2017
DOI: 10.1371/journal.pone.0179476
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of AAV8-mediated intrastriatal delivery of human cerebral dopamine neurotrophic factor in 6-OHDA-induced parkinsonian rat models with different disease progression

Abstract: Parkinson’s disease (PD) is a progressive and age-associated neurodegenerative disorder. Patients at different stages of the disease course have distinguished features, mainly in the number of dopaminergic neurons. Cerebral dopamine neurotrophic factor (CDNF) is a recently discovered neurotrophic factor, being deemed as a hopeful candidate for PD treatment. Here, we evaluated the efficacy of CDNF in protecting dopaminergic function using the 6-OHDA-induced PD rat model suffering from different levels of neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Both CDNF and MANF belonged to the novel dopaminergic neurotrophic factor, which have the ability to protect dopamine neurons from death (Ren et al, 2013; Tereshchenko et al, 2014; Voutilainen et al, 2015; Garea-Rodríguez et al, 2016; Tang et al, 2017; Wang et al, 2017). For instance, after delivery of CDNF by adeno-associated virus type 2/8 into 6-OHDA treated rat striatum, it improved rat’s behavior deficit and restored TH positive dopaminergic neurons in substantial nigra and increased fiber density in striatum (Ren et al, 2013; Wang et al, 2017). In this study, we observed a larger amount of CDNF present in MenSCs-CM than GDNF.…”
Section: Discussionmentioning
confidence: 99%
“…Both CDNF and MANF belonged to the novel dopaminergic neurotrophic factor, which have the ability to protect dopamine neurons from death (Ren et al, 2013; Tereshchenko et al, 2014; Voutilainen et al, 2015; Garea-Rodríguez et al, 2016; Tang et al, 2017; Wang et al, 2017). For instance, after delivery of CDNF by adeno-associated virus type 2/8 into 6-OHDA treated rat striatum, it improved rat’s behavior deficit and restored TH positive dopaminergic neurons in substantial nigra and increased fiber density in striatum (Ren et al, 2013; Wang et al, 2017). In this study, we observed a larger amount of CDNF present in MenSCs-CM than GDNF.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the spreading of the protein since there was minimal coverage of the striatum in comparison with the protein without viral vector (20,24). Other studies have shown positive results with AAV-CDNF: both AAV2-CDNF (25) and AAV8-CDNF (26) showed positive effects, but the latter was a much milder lesion than in the previous studies.…”
Section: Therapeutic Effects In Parkinson’s Diseasementioning
confidence: 59%
“…A flowchart of COMMAND is shown in Figure S4, along with examples of stereotaxic coordinates used by prior studies in Figure S5 (Aoi et al, 2000;Bilang-Bleuel et al, 1997;Cederfjä ll et al, 2015;Hattori et al, 1998;Horellou et al, 1994;Kilbourn et al, 1997;Kirik et al, 2000;Luo et al, 1999;Mandel et al, 1998;Rodrigues et al, 2003;Sacaan et al, 1991;Shults et al, 1996;Wang et al, 2017aWang et al, , 2017bZaczek et al, 1980).…”
Section: Star+methodsmentioning
confidence: 99%
“…Multi-bolus infusions improve control over spatial distribution, which reduces off-target toxicity. However, no standardized method to determine the optimal number, size, and location of boluses for a particular application exists (Cederfjä ll et al, 2015;Horellou et al, 1994;Kirik et al, 2000;Wang et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%